Pengaruh Metode Bermain Peran Terhadap Kemampuan Komunikasi (Bahasa Ekspresif) Anak Taman Kanak-Kanak Raudhatul Athfal Alauddin Makassar - Amri, Nur Alim (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2017)
Communication ability is a form of development that focuses on the language aspect. This study aims to obtain data about the description of the use of role playing methods, description of communication skills (expressive language) of children, as well as to test whether there is influence of role playing methods on the ability of expressive language children. By involving 20 students selected by simple random sampling technique, data were collected through initial and final test after the students were treated using role playing method then the data was analyzed through descriptive and inferential statistic in the form of Wilcoxon test. The results of data analysis showed that the expressive language ability of children increased after being treated through learning role play method.